Phonon-assisted resonant tunneling of electrons in graphene–boron nitride transistors - Vdovin, Evgeny E.; Mishchenko, A.; Greenaway, M.T.; Zhu, M.J.; Ghazaryan, D.; Misra, A.; Cao, Y.; Morozov, S.V.; Makarovsky, Oleg; Fromhold, T.M.; Patanè, Amalia; Slotman, G.J.; et al. (American Physical Society, 2016)
We observe a series of sharp resonant features in the differential conductance of graphene-hexagonal boron nitride-graphene tunnel transistors over a wide range of bias voltages between 10 and 200 mV. We attribute them to electron tunneling assisted by the emission of phonons of well-defined energy. The bias voltages at which they occur are insensitive to the applied gate voltage and hence independent of the carrier densities in the graphene electrodes, so plasmonic effects can be ruled out. The phonon energies corresponding to the resonances are compared with the lattice dispersion curves of graphene–boron nitride heterostructures and are close to peaks in the single phonon density of states.